2020
DOI: 10.1002/ana.25748
|View full text |Cite
|
Sign up to set email alerts
|

Faster Cortical Thinning and Surface Area Loss in Presymptomatic and Symptomatic C9orf72 Repeat Expansion Adult Carriers

Abstract: Objective C9orf72 expansion is the most common genetic cause of frontotemporal dementia (FTD). We examined aging trajectories of cortical thickness (CTh) and surface area in C9orf72 expansion adult carriers compared to healthy controls to characterize preclinical cerebral changes leading to symptoms. Methods Data were obtained from the Genetic Frontotemporal Dementia Initiative. T1‐weighted magnetic resonance imaging scans were processed with CIVET 2.1 to extract vertex‐wide CTh and cortical surface area (CSA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…A number of structural MRI studies elegantly depicted the profile of brain changes identifiable at different points of the preclinical phase and, more recently, investigated their rate of change over time [35,58,[62][63][64][65][66]. Overall, C9orf72 carriers display significant and widespread cortical volume loss compared to non-carriers, including frontal areas, temporo-insular cortices, associative parieto-temporal regions, and hippocampi approximately 20 to 25 years before their estimated disease onset [35,58,62,64,66]. At the subcortical level, there is a diffuse and massive volume loss in the thalamus, with prominent involvement of the pulvinar subnucleus [65], a profile which is coherent with what observed in the clinical phase [67].…”
Section: Biomarkers To Define the Preclinical Disease Trajectorymentioning
confidence: 99%
“…A number of structural MRI studies elegantly depicted the profile of brain changes identifiable at different points of the preclinical phase and, more recently, investigated their rate of change over time [35,58,[62][63][64][65][66]. Overall, C9orf72 carriers display significant and widespread cortical volume loss compared to non-carriers, including frontal areas, temporo-insular cortices, associative parieto-temporal regions, and hippocampi approximately 20 to 25 years before their estimated disease onset [35,58,62,64,66]. At the subcortical level, there is a diffuse and massive volume loss in the thalamus, with prominent involvement of the pulvinar subnucleus [65], a profile which is coherent with what observed in the clinical phase [67].…”
Section: Biomarkers To Define the Preclinical Disease Trajectorymentioning
confidence: 99%
“… 95 Among the many MRI measures evaluated in cross-sectional and longitudinal studies in FTLD, 96 , 97–103 volumetric MRI has shown the most promise in characterizing changes during the pre-symptomatic phase of f-FTLD (FTLD-CDR score = 0), with the topography of changes depending on the mutated gene. 94 , 98 , 99 , 101 Initial enthusiasm for use of tau PET ligands has faded, however, since none so far are adequately sensitive or specific for FTLD-associated tau fibrils; 104 current tau PET tracers do not seem to differentiate tau versus TDP-43 proteinopathies. Similarly, these PET tracers are not considered useful in s-FTLD associated with tau pathology (e.g.…”
Section: Pre-symptomatic Neurodegenerative Diseasesmentioning
confidence: 99%
“…About 40 neurological disorders have been found to be caused by STR expansion mutations [ 2 ], with some recent studies reporting the identification of additional pathogenic STR expansion loci through NGS or the more advanced third-generation long-read sequencing technologies [ 32 – 36 ]. While repeat expansion disorders typically have a delayed age of onset, pre-symptomatic individuals have been reported to exhibit subtle cognitive, behavioral, or structural changes in the brain [ 37 , 38 ]. Pre-symptomatic detection can help elucidate the pathophysiology and progression of the disease [ 39 ] and promote the development and timely implementation of disease-modifying interventions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%